Knee joint kinematics with dynamic augmentation of primary anterior cruciate ligament repair - a biomechanical study - Häberli, Janosch (J Exp Orthop, 2016)
BACKGROUND: Dynamic augmentation of anterior cruciate ligament tears seems to reduce anteroposterior knee translation close to the pre-injury level. The aim of the present study is to biomechanically investigate the course of translation during a simulated early post-operative phase. It is hypothesized that anteroposterior translation is maintained at the immediate post-operative level over a simulated rehabilitation period of 50’000 gait cycles. METHODS: Eight fresh-frozen human cadaveric knee joints from donors with a mean age of 35.5 (range 25–40) years were subjected to 50’000 cycles of 0°-70°-0° flexion-extension movements in a custom-made test setup. Anteroposterior translation was assessed with simulated Lachman/KT-1000 testing in 0°, 15°, 30°, 60° and 90° of flexion in knee joints treated with the novel technique initially and after 50’000 cycles testing. Statistical analysis was performed using the Wilcoxon Signed-Rank Test. The level of significance was set at p = 0.05. RESULTS: Anteroposterior translation changed non-significantly for all flexion angles between cycle 0 and 50’000 (p = 0.39 to p = 0.89), except for 30° flexion, where a significant increase by 1.4 mm was found (p = 0.03). CONCLUSION: Increase in anteroposterior translation of knees treated with this dynamic augmentation procedure is low. The procedure maintains translation close to the immediate post-operative level over a simulated rehabilitation period of 50’000 gait cycles and therefore supports anterior cruciate ligament repair during biological healing.